Sobre Soluções de Equações Elípticas Envolvendo o N-Laplaciano e Crescimento Crítico Exponencial - Araújo, Gustavo da Silva (2013)
In this work, we study existence, multiplicity and nonexistence of positive solutions, with respect to a positive parameter , for a class of quasilinear elliptic problems in bounded domains of RN, N 2, involving the N-laplacian operator and a nonlinearity f(t) which behaves as t, for some 2 (0;N1), when t ! 0+ and has critical exponential growth of Trudinger-Moser type at +1. In order to obtain the results, we have used minimax theorems, sub and supersolution methods and a refinement of the Trudinger- Moser inequality due to P.-L. Lions.